Physical and quality fruit parameters of new strawberry genotypes - Delazeri, Elói Evandro; Schiavon, Andressa Vighi; Becker, Tais Barbosa; Bonow, Sandro; Cantillano, Rufino Fernando Flores; Antunes, Luís Eduardo Corrêa (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate physical and chemical fruit parameters of new strawberry genotypes under field conditions. The study was carried out during the 2018 and 2019 seasons. Twelve genotypes from the breeding program of Embrapa and two commercial cultivars (Camino Real and Merced) were evaluated. The assessed parameters were: average fruit number, average fruit weight, soluble solids, titrable acidity, and the soluble solids/titrable acidity ratio. Among the studied strawberry genotypes, the 8-1, 35-22 ('BRS DC22'), 31-13, 7-5, and 32-2 selections produce more fruits per plant. Among the new genotypes, 'BRS DC25' (Fênix) and 31-13 present the best average fruit weight in both evaluated seasons. The highest sugar content is observed in genotypes 35-22 ('BRS DC22') and 65-2, whereas 8-1 and 'BRS DC25' (Fênix) show the highest acidity. The 7-5, 35-22 ('BRS DC22'), 34-2, and 35-6 genotypes present the best soluble solid/acidity ratio.
Keywords: Fragaria x ananassa; berry; cultivar; performance; seasonality